Ответ:
Объяснение:
1) m/n +(3m)/n=(4m)/n
2) (6c)/d -(2c)/d=(4c)/d
3) (8m+3)/(10m²) -(2m+3)/(10m²)=(8m+3-2m-3)/(10m²)=(6m)/(10m²)=3/(5m)
4)(2a-3b)/(6ab) -(9b+2a)/(6ab)=(2a-3b-9b-2a)/(6ab)=(-12b)/(6ab)=-2/a
5) (5m)/(m-n) +(5n)/(n-m)=(5m)/(m-n) -(5n)/(m-n)=(5m-5n)/(m-n)=(5(m-n))/(m-n)=5
6) (5n-1)/(20n) -(7n-8)/(20n) -(8n+7)/(20n)=(5n-1-7n+8-8n-7)/(20n)=(-10n)/(20n)=-1/2
7) n²/(n+5) -25/(n+5)=(n²-5²)/(n+5)=((n-5)(n+5))/(n+5)=n-5
8) (2x-y)/(x-y)² +(3x-4y)/(x-y)²=(2x-y+3x-4y)/(x-y)²=(5x-5y)/(x-y)²=(5(x-y))/(x-y)²=5/(x-y)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1) m/n +(3m)/n=(4m)/n
2) (6c)/d -(2c)/d=(4c)/d
3) (8m+3)/(10m²) -(2m+3)/(10m²)=(8m+3-2m-3)/(10m²)=(6m)/(10m²)=3/(5m)
4)(2a-3b)/(6ab) -(9b+2a)/(6ab)=(2a-3b-9b-2a)/(6ab)=(-12b)/(6ab)=-2/a
5) (5m)/(m-n) +(5n)/(n-m)=(5m)/(m-n) -(5n)/(m-n)=(5m-5n)/(m-n)=(5(m-n))/(m-n)=5
6) (5n-1)/(20n) -(7n-8)/(20n) -(8n+7)/(20n)=(5n-1-7n+8-8n-7)/(20n)=(-10n)/(20n)=-1/2
7) n²/(n+5) -25/(n+5)=(n²-5²)/(n+5)=((n-5)(n+5))/(n+5)=n-5
8) (2x-y)/(x-y)² +(3x-4y)/(x-y)²=(2x-y+3x-4y)/(x-y)²=(5x-5y)/(x-y)²=(5(x-y))/(x-y)²=5/(x-y)